2022
DOI: 10.1371/journal.pone.0267376
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to facemask adherence in the covid-19 pandemic in Pakistan-A cross-sectional survey

Abstract: Objective To explore perceived barriers associated with facemask adherence to prevent spread of COVID-19 spread in Pakistani population. Methodology A cross sectional study was conducted from 25-July 2020 to 5-August 2020. Participants of both genders of age >17 years, currently residing in Pakistan, who had access to internet and understood English were included in the survey. The survey was designed on Google form and was distributed digitally across different areas of Pakistan via social media. Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Although the multifaceted benefits of face masks are sufficiently known, the frequency and acceptance of wearing masks remain controversial among the general population due to the challenges posed by wearing face masks for long periods. According to recent studies, the most common reported hurdles to face mask adherence were physical and social discomfort, difficulty breathing, glasses fogging, financial reasons, headache, perioral dermatitis, facial itching and rash/irritation (Abid et al 2022;Fikenzer et al 2020;Scarano et al 2020). Furthermore, face masks hindered face recognition and communication, both verbal and non-verbal, affecting emotional signalling, especially between teachers and students in educational facilities (Carbon 2020; Spitzer 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although the multifaceted benefits of face masks are sufficiently known, the frequency and acceptance of wearing masks remain controversial among the general population due to the challenges posed by wearing face masks for long periods. According to recent studies, the most common reported hurdles to face mask adherence were physical and social discomfort, difficulty breathing, glasses fogging, financial reasons, headache, perioral dermatitis, facial itching and rash/irritation (Abid et al 2022;Fikenzer et al 2020;Scarano et al 2020). Furthermore, face masks hindered face recognition and communication, both verbal and non-verbal, affecting emotional signalling, especially between teachers and students in educational facilities (Carbon 2020; Spitzer 2020).…”
Section: Introductionmentioning
confidence: 99%